SmartGrid with advanced IT for power system applications - Ong, Chang Jie. (2009)
Electric power infrastructures, also known as power grids, are the largest remaining artifacts from the Industrial Revolution age and are due for a smart upgrade. Think of the smart grid as the internet that is brought to the power grids which computer technologies and internet communications can be deployed within the very near future or are already deployed today. However there are many computing and communication technologies available to implement a smart grid design. This project experiments with a new approach for power system applications. A prototype system has been developed to demonstrate the potential of using Java 2 Enterprise Edition (J2EE) and its remarkable complete runtime library (API), along with open source applications to realize the interoperability between the various entities within a smart grid. The prototype system is broadly subdivided into three main sections to implement a distributed object architecture and a web application framework. The developed prototype system does achieve its intended goals but its viability for use in production systems with high user loads and incorporation of hardware components remain to be seen and would be a point of interest for future recommendations.